The Ethical Subject and Willing Subject in the Tractatus: an Alternative to the Transcendental Reading. - Fairhurst, Jordi (Philosophia, 2019)
The Transcendental Reading of the Tractatus argues that Wittgenstein endorses, under the notion of 'metaphysical subject', the existence of a willing subject as a transcendental condition of ethics and representation. Tejedor aims to reject this reading resorting to three criticisms. (i) The notion of 'willing subject' does not appear explicitly in, nor can it be deduced from, the Tractatus, (ii) the metaphysical subject and the willing subject are not synonymous or analogous notions and, finally, (iii) Wittgenstein abandons the notion of 'willing subject' at the end of the Notebooks. The aim of this article is twofold. Firstly, it analyzes the critique introduced by Tejedor and presents three problems that demonstrate that Tejedor's critique cannot adequately reject the Transcendental Reading. Secondly, it sets forth an alternative reading of the Tractatus that overcomes the issues that stem from the Transcendental Reading. This alternative reading conceives the metaphysical subject as an ethical subject and a willing subject. Additionally, it advances an alternative account of the transcendental character of ethics that does not defend the existence of a transcendental subject understood as a condition of ethics and representation in the Tractatus.